DIGITALISASI LAYANAN SAMSAT: Peningkatan Kepatuhan Pajak Kendaraan Bermotor Melalui e-Samsat di Kabupaten Muna - Suriyani BB; La Ode Agus Said; Astriana Syaqira (Journal Publicuho, 2024)
The purpose of this study is to determine the DIGITALIZATION OF SAMSAT SERVICES: Increasing Motor Vehicle Tax Compliance Through e-Samsat in Muna Regency. This research method is qualitative research with a descriptive approach. The research informants consisted of 9 people. Data collection techniques through interviews, direct observation, and documentation. Qualitative descriptive research is research that aims to describe events or phenomena that occur in the field and present data systematically, factually, and accurately regarding the facts or phenomena that occur in the field. The results of the analysis of the implementation of the e-SAMSAT system in Muna Regency first have not been fully implemented properly such as the content dimension, in addition, the dimensions of timeliness and ease of use are effective. However, this system has not had a major influence on taxpayer compliance. There are still obstacles in the implementation of the e-SAMSAT system in paying taxes, including Cultural or historical reasons, Lack of information or counselling by the Government to taxpayers and Individual Atmosphere. Gradual and comprehensive socialization is needed from related officials, namely the Muna Regency SAMSAT Public Relations Team in public places by opening stands to introduce the existence of the e-SAMSAT system service so that taxpayers can be aware of their obligations.